Productivity and carcas traits of pigs fed with solid-state fermented apple pomace and an enzymatic complex - Chamorro-Ramírez, Francisco Héctor; García-Macías, José Arturo; Durán-Meléndez, Lorenzo Antonio; Peña-González, Esmeralda Mónica; González-Sánchez, José Fernando (Ecosistemas y Recursos Agropecuarios, 2017)
The productive performance of pigs fed with solid-state fermented apple pomace (FAP) and an enzymatic complex (ENZ) was evaluated. Twenty-four Landrace x York (38.9±3.6 kg) pigs fed ad libitum with different diet treatments including FAP and ENZ; T0-0 (0 g kg-1 FAP – 0 g kg-1 ENZ), T0-1 (0 g kg-1 FAP + 1 g kg-1 ENZ), T50-0 (50 g kg-1 FAP + 0 g kg-1 ENZ), T50-1 (50 g kg-1 FAP + 1 g kg-1 ENZ), T100-0 (100 g kg-1 FAP + 0 g kg-1 ENZ) and T100-1 (100 g kg-1 FAP + 1 g kg-1ENZ). Feed intake, F:G ratio, growth characteristics, the return on investment by monetary unit (profitability index, PI) and carcass traits were evaluated. Productivity was not affected by FAP or ENZ (P>0.05) as well as feeding characteristics (P>0.05). Hot dressing percent was affected by ENZ (P=0.0497). T100-0 showed similar value to T0-0. Primary cuts yield was not negatively affected (P>0.05). The best PI was obtained to T50–0 in growing phase. FAP improved PI only in growing phase and ENZ combined with FAP showed variant PI. The results showed that FAP may be considered as an adequate option to feeding pigs maintaining animal productivity.